Welfare Based Evaluation of Monetary Policy Conduct in the Czech Republic - Nguyen, Nhat Linh; Janíčko, Martin, 1983-; Potužák, Pavel; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2018)
This thesis provides a welfare analysis of the inflation-targeting regime and its variationsthat take the nominal exchange rate stability into the consideration. The analysis donein this work aims to answer a question, whether there is a room for improvements in thecurrent Czech monetary policy framework. In particular, this work utilizes a dynamicstochastic general equilibrium (DSGE) model of a small open economy and compares thecurrent inflation-targeting regime to its hypothetical variations that incorporate nominalexchange rate stabilization. The results presented in this work suggest that the incorporationof the exchange rate stability could be beneficial in terms of welfare. However, asindicated by a robustness test, these results are sensitive to the calibration of the modeland further research on this topic is advisable before making any conclusions. The othercontribution of this thesis is showing how to solve a small open economy model withoutlog-linearization. This allows solving the presented small open economy model and itsvariations using the higher-order approximation methods.
Vedoucí práce: Martin Janíčko
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomická analýza [obor dipl. práce]; diplomové práce; master's theses